An overview on comparative engine performance and emission characteristics of different techniques involved in diesel engine as dual-fuel engine operation. (July 2016) - Abedin, M.J.; Imran, A.; Masjuki, H.H.; Kalam, M.A.; Shahir, S.A.; Varman, M.; Ruhul, A.M.
Abstract: Abatement of pollutant emissions from transport sector is one of the major concerns throughout the globe. One of the main technical challenges for transportation sector is to reduce pollutant emissions from diesel engine and to meet satisfactory engine performance, simultaneously. Different technical changes have been introduced in diesel engine to apply alternative biofuels to reduce pollutant emissions. Blend, fumigation, and emulsion are three different dual fuel engine operation techniques, which have been introduced in diesel engine for biofuel application. In the blend mode, biofuel and diesel are mixed in desired proportions before injecting into cylinder, whereas in fumigation mode, biofuel is injected into intake manifold to mix with the intake fresh air. Emulsion is a process wherein two immiscible substances are mixed together. This study provides a comprehensive review on these three techniques of biofuel injection and their comparative effects on the engine performance and emissions. From these studies, it is found that the effects on engine performance and emission mostly depend on biofuel properties. Increase in break specific fuel consumption (BSFC) is common in each method due to the lower calorific value of biofuels. Brake thermal efficiency (BTE) decreases in blend and fumigation modes, but increases in emulsion mode. Nitrogen oxides (NO x ) emissions decrease in fumigation and emulsion modes, but increase in blend mode. Carbon monoxide (CO) and Hydro carbon (HC) emissions increase in fumigation and emulsion modes, but decrease in blend mode. Particulate Matter (PM) emission decreases in all three modes.